Coverage of Ancient and Modern Sports Games in Periodical Press Materials (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the issues related to the coverage of ancient and modern sports in periodical press materials. The importance of preserving national and world sports heritage and passing it on to the younger generation through the coverage of ancient sports in the press is highlighted. It also examines the widespread promotion of modern sports through the media, the results of competitions, the achievements of athletes, and their role in the formation of sports culture in society. The methods of coverage of ancient and modern sports, information delivery techniques, and their impact on the worldview of students are analyzed.